2022
DOI: 10.3389/fimmu.2022.939504
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of exosomal miRNAs and membrane proteins in acute HIV-infected people

Abstract: Exosomes play an important role during human immunodeficiency virus (HIV) acute infection. Yet, information regarding its cargo and its association with HIV rapid progressors (RPs) and typical progressors (TPs) remain largely unknown. In this study, exosomal miRNAs sequencing and mass cytometry were used to identify differential exosomal miRNAs and membrane proteins that participate in the pathogenesis of TPs and RPs. We discovered that miR-144-5p, miR-1180-3p, miR-451a, miR-362-5p, and miR-625-5p are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs) are endogenous, noncoding RNAs that mediate mRNA cleavage, translational repression, or mRNA destabilization [ 32 ]. Increasing evidence has demonstrated that miRNAs exert biological functions by EVs transmission to modulate the host immune response in viral infection [ 33 , 34 ]. Zhang et al showed that the SARS-CoV-2 spike protein induced platelet activation by ACE2 binding to enhance thrombosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous, noncoding RNAs that mediate mRNA cleavage, translational repression, or mRNA destabilization [ 32 ]. Increasing evidence has demonstrated that miRNAs exert biological functions by EVs transmission to modulate the host immune response in viral infection [ 33 , 34 ]. Zhang et al showed that the SARS-CoV-2 spike protein induced platelet activation by ACE2 binding to enhance thrombosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a defense mechanism against HIV, and Nef bypasses autophagy-mediated restriction by promoting ubiquitination of BCL2, an autophagy inhibitor, through the Parkin/PRKN pathway ( 48 ). C-C chemokine receptor type 5 (CCR5), a coreceptor of HIV-1, is also detected in exosomes secreted by HIV-1-infected cells, and HIV-1 may transfer receptor molecules through exosomes to alter the expression of viral receptors on the cell surface, which is conducive to HIV-1 infection of tissues with endogenous CCR5 expression loss ( 49 ), and the differential expression of CCR5 molecule on the exosome membrane may help to distinguish HIV patients with different progression types ( 50 ). Group-specific antigen (Gag) is also contained in exosomes released by HIV-infected cells.…”
Section: Exosomes In Virus Infectionmentioning
confidence: 99%